1997
DOI: 10.1177/001440299706300207
|View full text |Cite
|
Sign up to set email alerts
|

Self-Determination and Positive Adult Outcomes: A Follow-up Study of Youth with Mental Retardation or Learning Disabilities

Abstract: There is increased emphasis on self-determination as an important outcome for youth with disabilities if they are to achieve positive adult outcomes after they leave school. However, the causal link between self-determination and positive adult outcomes has remained untested. The Arc conducted a follow-up study of students with mental retardation or learning disabilities for whom data regarding self-determination had been collected prior to their high school exit. Data regarding adult outcomes for these studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
311
1
15

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 447 publications
(341 citation statements)
references
References 8 publications
10
311
1
15
Order By: Relevance
“…Given the preliminary nature of this study, further research is needed to examine the role of each of these constructs. The role of self-determination needs to be investigated further, given that a large body of research suggests that self-determination contributes to positive outcomes for students with disabilities (Wehmeyer & Palmer, 2003;Wehmeyer & Schwartz, 1997. As there may have been issues with the measurement of self-determination in this study, that problem may account for failure of self-determination to significantly predict life satisfaction.…”
Section: Mean Level Differences As Shown Inmentioning
confidence: 95%
See 1 more Smart Citation
“…Given the preliminary nature of this study, further research is needed to examine the role of each of these constructs. The role of self-determination needs to be investigated further, given that a large body of research suggests that self-determination contributes to positive outcomes for students with disabilities (Wehmeyer & Palmer, 2003;Wehmeyer & Schwartz, 1997. As there may have been issues with the measurement of self-determination in this study, that problem may account for failure of self-determination to significantly predict life satisfaction.…”
Section: Mean Level Differences As Shown Inmentioning
confidence: 95%
“…For example, Huebner (1991) found that students who reported high life satisfaction also tended to score more adaptively on measures of locus of control, and Ash and Huebner (2001) found that locus of control mediated the relationship between acute negative life events and chronic stressors and life satisfaction in adolescents. And, although the functional theory of self-determination has never been evaluated in terms of its contribution to life satisfaction, it has been shown to contribute to a more positive quality of life (Wehmeyer & Schwartz, 1998) and to positive postschool outcomes for youth with cognitive disabilities (Wehmeyer & Palmer, 2003;Wehmeyer & Schwartz, 1997). Thus, we sought to further this knowledge base and examine the role of hope, optimism, and locus of control, as well as the potential role of the functional theory of self-determination, in predicting adolescent's life satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, in other countries, such as the United States, different studies have been carried out to establish the link between a greater command of abilities relating to self-determination and the greater or lesser achievement of results in one's own objectives in adulthood (work, independent life, community participation). Thus, Wehmeyer and Schwartz (1997) and Wehmeyer and Palmer (2003), in studies that relate level of self-determination to achieving positive objectives in adult life, conclude that pupils with a higher score in self-determination tests demonstrate greater probability of obtaining employment and a higher salary after completing their education. Both of the above involved longitudinal studies in which data on self-determination was collected a year prior to the end of secondary education, contrasting these with the situation one year after data collection in the former case and three years in the latter.…”
Section: Secondary Education and Labour Market Inclusion What Does Tmentioning
confidence: 99%
“…It is generally accepted (and, as discussed subsequently, there is empirical evidence) that one factor contributing to positive outcomes in the lives of students with disabilities is enhanced self-determination (Wehmeyer & Schwartz, 1997). 2.…”
Section: How Are Quality Of Life and Self-determination Related?mentioning
confidence: 99%
“…Wehmeyer and Schwartz (1997) measured the selfdetermination of 80 youth with cognitive disabilities (mild mental retardation or learning disability). One year after these students left high school, they and their families were contacted to determine status in several areas, including student living arrangements, current and past employment situations, post-secondary education status, and community integration outcomes.…”
Section: Are Self-determination and Quality Of Life Important For Stumentioning
confidence: 99%